ความรู้ ทัศนคติ และการปฏิบัติในการใช้ยาของผู้ป่วยนอกที่มารับบริการจากโรงพยาบาลของรัฐในภาคใต้ของประเทศไทย - อรุณพร อิฐรัตน์ (มหาวิทยาลัยสงขลานครินทร์, 2024)
The objectives of this survey research were to study the knowledge, attitude, and practice in drug use of patients who obtained service from the out-patient department of government hospitals in southern Thailand and to find the relationship between the population, social and economic factors, sources of knowledge, and drug-using behaviors of the patients. A simple random sampling was used to select 1,819 out-patients receiving service from government hospitals in southern Thailand. A questionnaire which had been tested for its content validity and objectivity was used. The data were analyzed by the chi-square test, frequency, and percentage. The results of the study were as follows: Of the sample group of 1,819 out-patients, most of them were female (60.5 percent), Buddhist (83.8 percent); more than 75.0 percent of them had a monthly income of less than 5,000 baht, had finished primary education (39.1 percent) and 64.8 percent lived outside municipal areas. The source of knowledge for most of the sample group was medical doctors (38.2 percent), medical labels (12.6 percent), and only 9.1 percent of the sample group obtained the drug knowledge from pharmacists which is the most correct source of knowledge. Most of the sample group (49.6 percent), chose to obtain service from a government hospital as their first choice; a private clinic (24.0 percent) for reasons of convenience, speed of service and a short distance from home. More than 50 percent of the population in the South had a moderate level of correct knowledge and attitude but their behaviors in using drugs correctly was at a high level. The factors relative to knowledge, attitude, and methods in drug use were age, occupation, income, education, residence, and source of knowledge. That is to say that the samples whose ages were between 21-30 years who were government officials or state enterprise employees with a monthly income of 5,000 baht or more, holders of a bachelor's degree or higher, lived in an urban area had a high level of correct knowledge, attitude and practice in drug use. Pharmacists were the most correct source of knowledge (50.0 percent) followed by mass media and medical labels which accounted for 40.5 and 39.1 percent, respectively. However, mass media was the source of knowledge which provided the sample group with correct attitude more often than pharmacists, 43.3 and 41.6 percent, respectively. Public Health Messengers and Public Helath Volunteers were the sources of knowledge which provided most of the sample groups with correct practice in drug use (93.4 percent) followed by mass media (92.5). The source of service which provided the most correct knowledge, attitude, and practice in drug use was private clinics. Religion was another factor relative to correct attitude and practice, but not to the knowledge of the sample group. In addition, it was found that more females than males had correct practice in drug use which was statistically significant at the level of 0.05. As for the relationship between knowledge, attitude, and practice in drug use, the coefficient value was found to be very low and was not statistically significant at the level of 0.05.